Male versus female skin: What dermatologists and cosmeticians should know - S. Rahrovan, MD, MPH; F. Fanian, MD, PhD; P. Mehryan, MD; P. Humbert, MD, PhD; A. Firooz, MD (Wolters Kluwer, 2018)
Introduction: The skin is important for the perception of health and beauty. Knowledge of the physiological, chemical, and biophysical differences between the skin of male and female patients helps dermatologists develop a proper approach not only for the management of skin diseases but also to properly take care of cosmetic issues. The influence of genetic and environmental factors on skin characteristics is also critical to consider. Methods: A literature search of PubMed and Google was conducted to compare the biophysical and biomechanical properties of the skin of male and female patients using the keywords ''skin'', ''hydration'', ''water loss'', ''sebum'', ''circulation'', ''color'', ''thickness'', ''elasticity'', ''pH'', ''friction'', ''wrinkle'', ''sex'', ''male'', and ''female''. Results: A total of 1070 titles were found. After removing duplications and non-English papers, the number was reduced to 632. Of the 632 titles, 57 were deemed suitable for inclusion in this review. The studies show that the skin parameters of hydration, transepidermal water loss, sebum, microcirculation, pigmentation, and thickness are generally higher in men but skin pH is higher in women. Conclusions: These parameters can be considered as age markers in some cases and are susceptible to change according to environment and life style. Biometrological studies of the skin provide useful information in the selection of active principles and other ingredients of formulations to develop a specific approach for cosmetic treatments.